An Analysis Of Figurative Language Used In Bruno Mars’ Songs - Azhari, Muh Kholiki; Mahyuni; Baharuddin (Journal of Authentic Research, 2025)
This study investigates the use of figurative language in Bruno Mars' song lyrics, focusing on how various figurative expressions enhance emotional depth and convey meaning in his works. Guided by Knickerbocker and Reninger's framework, this study uses a qualitative descriptive approach supported by content analysis to identify, classify, and interpret figurative expressions in four Bruno Mars albums: Doo-Wops and Hooligans, Unorthodox Jukebox, 24K Magic, and An Evening with Silk Sonic. The analysis is conducted in four systematic stages: identification, categorization, interpretation, and contextual analysis of the figurative language found in the lyrics. This study is motivated by the growing recognition that song lyrics, particularly in popular music, function as a form of poetic and cultural expression. Bruno Mars was chosen as the focus of the analysis because of his global influence, genre diversity, and the sophistication of his lyrics, which often involve the creative use of figurative language to express universal human experiences such as love, heartbreak, ambition, and joy. The four albums were chosen to explore how the diversity of figurative language reflects his artistic evolution and emotional range throughout his career. The findings reveal eight distinct types of figurative language, with metaphor and hyperbole being the most dominant. These devices serve to intensify emotions, create vivid imagery, and accentuate expressive nuances in his songwriting, while personification, simile, irony, and symbolism add depth and aesthetic variety. The figurative language in Bruno Mars' lyrics serves as an artistic and communicative device that bridges literal meaning and emotional resonance. This study is expected to contribute to the fields of linguistics and stylistics by demonstrating how popular music integrates creative language to express complex emotions and cultural meanings. It also provides a methodological model for analyzing figurative language in various musical works. Furthermore, this research offers pedagogical value for non-native English speakers, helping them interpret English song lyrics more accurately and appreciate their figurative meanings, thereby preventing misinterpretation and enriching linguistic competence and cultural understanding.